Ritanserin in depressives: dysthymic type and adjustment disorder with depressed mood (depressive neurosis): a double blind placebo controlled doser range finding study - Bekker, Hendi (My University, 2016)
In the first part of the dissertation a literature survey is done, looking at 1. An overview of dysthymic disorder. 2. An overview of serotonin and its involvement in psychiatric disorder [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Medicine in Psychiatry. Johannesburg, March 1991.
Keywords: Serotonin.; Serotonin Antagonists.; Depressive Disorder -- drug therapy.